Performing leadership: Observations from the world of music - Ralph Bathurst; Donna Ladkin (Administrative Sciences, 2012)
This paper explores leadership as an emergent social process. We begin by discussing and contesting the tradition privileging linear management processes, and offer as a counterpoint accounts of distributed leadership out of which our focus on leadership as a plural process grows. Our concept of leadership as a plural process is enriched by an inquiry into musical ensembles with formal leaders as well as those which are leaderless that find ways of moving collectively towards shared goals. The specific issues that we explore are: personal preparation, expressing readiness to begin, establishing a way of operating, and dealing with unexpected problems as they arise. We conclude by speculating about how these elements could inform our understanding of how leadership arises from teams beyond the musical world.
Keywords: 350; ensemble-consciousness; group leadership; hierarchy; jazz; narrative; orchestra; structure